DNA fingerprinting of Trypanosoma vivax isolates rapidly identifies intraspecific relationships - Dirie, M.F.; Murphy, N.B.; Gardiner, Peter R. (Wiley, 1993)
ABSTRACT. Using the polymerase chain reaction and arbitrarily selected oligonucleotide primers of 10 or 11 bases, we have amplified DNA sequences from Trypanosoma vivax parasites isolated from South America and Africa. On the basis of polymorphisms in the DNA fingerprints generated by three of the primers, the parasites could be separated into two major groups, one comprising T. vivax isolates from Kenya and the second including all the other T. vivax parasites (from Colombia, The Gambia, Nigeria and Uganda). One of these three primers (ILo 525) also gave isolate‐specific DNA fingerprints for the parasites for the parasites tested, which will allow the use of this technique both in the species identification and discrimination of T. vivax parasites.